Respuesta :
Answer:
Explanation:
Let the initial rotational inertia be I and final rotational inertia be I / 6 .
Let the initial angular velocity be ω₁ and final angular velocity be ω₂.
Applying conservation of angular momentum law
I x ω₁ = I / 6 x ω₂
6 ω₁ = ω₂
initial rotational kinetic energy = 1/2 I x ω₁ ²
Final rotational kinetic energy = 1/2 ( I / 6 ) x ω₂ ²
Final rotational kinetic energy / initial rotational kinetic energy
= ( 1 / 6 ) x ω₂ ² / ω₁ ²
= ω₂ ² / 6ω₁ ²
= 36 ω₁ ² / 6ω₁ ²
= 6 .
The ratio will be "6". A further solution is below.
Let,
The initial rotational inertia,
- [tex]\omega_1 = 1[/tex]
The final rotational inertia,
- [tex]\omega_2 = \frac{1}{6}[/tex]
By applying the conservation of angular momentum law, we get
→ [tex]1\times \omega_1 = \frac{1}{6}\times \omega_2[/tex]
→ [tex]6 \ \omega_1 = \omega_2[/tex]
Now,
Initial rotational K.E = [tex]\frac{1}{2}1\times \omega_1^2[/tex]
Final rotational K.E = [tex]\frac{1}{2} (\frac{1}{6} )\times \omega_2^2[/tex]
hence,
→ [tex]\frac{Final \ rotational \ K.E}{Initial \ rotational \ K.E} = \frac{(\frac{1}{6} )\times \omega_2^2}{\omega_1^2}[/tex]
[tex]= \frac{\omega_2^2}{6 \omega_1^2}[/tex]
[tex]= 6[/tex]
Thus the answer above is right.
Learn more:
https://brainly.com/question/25347365